The construction of the pre-Hispanic past of Colombia - Botero, C; Botero, Clara Isabel (2001)
This study examines the construction of the pre-Hispanic past of Colombia from the 1820's to the 1940s. It describes and analyses the reception, dissemination and appropriation of knowledge about ancient Colombian societies. It analyses the works by Colombian and foreign antiquarians, savants and archaeologists and the formation of Colombian pre-Hispanic collections in the Museo Nacional in Bogotá and in three major European Museums : the Museum für Völkerkunde in Berlin, the British Museum in London and the Musée d'Etnographie du Trocadero in Paris. The study shows the ways Colombian archaeological objects were viewed in the course of this history. At its outset, during the Colonial period, Colombian pre-Hispanic objects were first seen as "Idols of the devil"; in Europe, they were initially considered as curiosities and as works or art. During the nineteenth century, archaeological objects began to be valued and interpreted by Colombian and foreign scholars and antiquarians as antiquities and also as art objects. How Colombia was presented and represented in the National Museum in Bogotá and in international exhibitions during the second half of the nineteenth century is described and analysed, and how pre-Hispanic artefacts came to form part of a representation of Colombia nationally and internationally. The final chapters deal with the first four decades of the twentieth century, when the pre-Hispanic period received a new degree of recognition in Colombia with the enactment of official measures for the protection of antiquities, the building of archaeological collections in the National Museum in Bogotá and in research done by foreign and Colombian archaeologists, which began to define archaeological areas scientifically. The final chapter examines the background for the establishment of the Colombian scientific tradition in archaeology during the 1930's with the creation of the Servicio Arqueológico Nacional, the Institute Etnológico Nacional and two archaeological museums, the Museo Arqueológico Nacional and the Museo del Oro.